Integrative coordination and state-reinforced adaptive governance of small-scale irrigation systems in the Yangtze River basin, China - Ying Chai; Xiaoshan Chen; Su Pan; Yunmin Zeng (Ecology and Society)
The self-governance of the commons by local communities often faces significant challenges during large-scale disturbances, necessitating a shift toward adaptive governance regimes. This study examines the role of state-reinforced adaptive governance in enhancing the resilience of small-scale irrigation systems, with a focus on the Yangtze River Basin in China during the 2022 summer drought in China. We explored three adaptive governance pathways: HV-coordination, H-coordination, and V-coordination. Our findings reveal that adaptive governance, particularly through integrative coordination (HV-coordination), enabled the irrigation community to effectively maintain resilience during the drought by transitioning to a state-reinforced adaptive-governance model. This transition involved complex water management interventions by the government across the basin, driven by changes in relative prices associated with agricultural production and food security. The co-production process, characterized by integrative coordination between the basin authority and the irrigation community along both vertical and horizontal dimensions was pivotal in enforcing adaptive governance. Key factors contributing to the success of state-reinforced adaptive governance included access to meteorological information, strong governance within the community, alignment of local institutions with scientific knowledge, and significant capital investment for infrastructure connectivity and upgrades.